Comparison of reproductive performance of Ongole cross and Ongole-Limousin cross in Bekri district, Central Lampung regency, Lampung province, Indonesia - Sukma, Puspa Permata; Ismudiono Ismudiono; Sri Mulyati; Pudji Srianto; Sri Pantja Madyawati; Ira Sari Yudaniayanti; Abdullah Hasib (Ovozoa: Journal of Animal Reproduction, 2024)
This study aims to compare the reproductive performance of the Ongole cross (PO) and Ongole-Limousin cross (Limpo) on smallholder farmer in Bekri district, Central Lampung regency, Lampung province, a Indonesia. This study used 30 PO cows, 30 Limpo F1 (first filial) cows and 30 Limpo F2 cows. Sample cows had at least two parities and had never had a history of reproductive disorders. This study used primary and secondary data related to sample cows. Primary data was obtained from interviews with farmers and secondary data was obtained from the Department of Plantations, Livestock and Fisheries of Central Lampung regency, and inseminator recording. Data were described descriptively and analyzed using a one-way Analysis of Variance in Statistical Product and Service Solution (SPSS) version 23. The result showed that the services per conception of Limpo F2 cows was higher (p <0.05) than for PO and Limpo F1 cows. Days open and calving interval for Limpo cows (F1 and F2) were longer (p <0.05) than for PO cows. Days open and calving interval for Limpo F1 cows were not significantly different (p >0.05) than for Limpo F2 cows. Reproductive performance of PO cows was better compared to Limpo F1 and Limpo F2 cows. However, there was a data discrepancy between reproductive performance and data on rearing systems, feed quality, and signs of estrus observed by farmers. It could be concluded that PO cows had better reproductive performance than Limpo cows.